PENGARUH EKSTRAK JAMBU BIJI MERAH (Psidium guajava Linn) TERHADAP KUALITAS DAGING SAPI DALAM PROSES CURING - Haradito, Aditya; Utami, Rohula; Nursiwi, Asri (Universitas Sebelas Maret (UNS), 2021)
Curing is a method that can be used to maintain the quality of beef. The curing method uses nitrate and nitrite compounds, which have useful roles in the curing process. However, those compounds have a side effect on the body if consumed continuously, which causes cancer disease (carcinogenic). This harmful carcinogenic property can be controlled by the addition of ascorbic acid. Ascorbic acid is commonly found in several fruits, one of which is red guava (Psidium guajava L). Therefore, this study aims to find out the most optimal addition of red guava extract in maintaining the beef qualities with curing treatment on the parameters of water content, pH, whc, texture, color, ascorbic acid, and nitrite residue. This study was conducted using a Completely Randomized Design with the various concentration of red guava extract (0%-5%) and observed at soaking times of 0, 2, 4, and 6 days. The analysis was performed by twice of sample repetition and analysis repetition. The results of the analysis were statistically analyzed by One Way ANOVA continued with the DMRT test if the results were significantly different (α = 0.05). Based on the results of the study, the higher of concentration in red guava extract, the pH, water content, whc, b* color, a* color, nitrite residue were smaller while the hardness, springiness, cohesiveness, L* color, a* color, the ascorbic acid content in curing were higher. The chosen treatment due to the test parameter in this study was the addition of 4% concentration in red guava extract in the curing process with 2 days soaking times.